CLEANED Technical Workshop Report. [De Ferme Framboos, Saint-Agatha Rode − south of Leuven, Belgium] - Musau, Emmanuel Mwema (Bioversity International and the International Center for Tropical Agriculture, 2022)
A technical team from the Alliance Bioversity-CIAT and International Livestock Research Institute arranged for an intensive working session in Belgium to reflect on the progress, refine and improve the CLEANED eXtRa tool. The discussions were part of the CGIAR research initiatives on Livestock, Climate and Systems Resilience (LCSR) and Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING) and succeeded the earlier workshop in 2020 at Kapiti station in Kenya under the Livestock CRP. We thank donors who contribute to the One CGIAR trust fund.